ENVIRONMENTAL HEALTH RISK ASSESSMENT OF MERCURY EXPOSURE IN RED SNAPPER FISH TO COGNITIVE FUNCTION DISORDERS - Ayu Rofia Nurfadillah; Tri Septian Maksum (Universitas Negeri Gorontalo, 2021)
Gold mining activities produce mercury waste which is very toxic. Mercury can enter the waters and accumulate in fish, and if consumed it can cause health problems, for example neurological dysfunction. Research objective was to analyze the risk of mercury in red snapper on cognitive dysfunction at the community in Bilato Sub-District, Gorontalo District. This study was observational study with cross-sectional design and Environmental Health Risk Analysis (EHRA). The population is all red snapper that live and forage in Bilato waters, and buyers who consume red snapper sold in Bilato Traditional Market. The research sample was red snapper which was sold in it, and 100 respondents were obtained using purposive sampling technique. Mercury content data were obtained through laboratory test results, and respondent data were collected through interviews. Data analysis technique used EHRA method, chi-square and spearman correlation test. The results showed that level of mercury in red snapper was 0.00035 ppm, 68.0% of respondents consumed it and 92.0% had impaired cognitive function. The realtime RQ values were 0.00223 (no risk) and 3.43 (risky) for lifetime RQ. There is a relationship between consumption of red snapper and impaired cognitive function (p=0.043). Meanwhile, the unrelated variables were frequency of consumption (p=0.772), amount of consumption (p=0.602), and duration of consumption (p=0.843). It's recommended that the public consume more varied fish to minimize accumulation of mercury in the body.